Electron scattering in hot-dense plasmas - Zammit, Mark; Fursa, Dmitry; Bray, Igor (2012)
Hot-dense plasmas have direct industrial applications in inertial confinement fusion. We have used the convergent close-coupling (CCC) method to investigate electron scattering off hydrogen and helium atoms in a hot-dense weakly coupled (Debye) plasma. The Yukawa-type Debye-Hückel potential has been used to describe the plasma screening effects. Integrated excitation, total ionization and total cross sections have been calculated over a broad range of energies and various Debye lengths, D.